Linkage map of Escherichia coli K-12, edition 8. - Bachmann, B J (1990)
The linkage map of Escherichia coli K-12 depicts the arrangement of genes on the circular chromosome of this organism. The basic units of the map are minutes, determined by the time-of-entry of markers from Hfr into F- strains in interrupted-conjugation experiments. The time-of-entry distances have been refined over the years by determination of the frequency of cotransduction of loci in transduction experiments utilizing bacteriophage P1, which transduces segments of DNA approximately 2 min in length. In recent years, the relative positions of many genes have been determined even more precisely by physical techniques, including the mapping of restriction fragments and the sequencing of many small regions of the chromosome. On the whole, the agreement between results obtained by genetic and physical methods has been remarkably good considering the different levels of accuracy to be expected of the methods used. There are now few regions of the map whose length is still in some doubt. In some regions, genetic experiments utilizing different mutant strains give different map distances. In other regions, the genetic markers available have not been close enough to give accurate cotransduction data. The chromosome is now known to contain several inserted elements apparently derived from lambdoid phages and other sources. The nature of the region in which the termination of replication of the chromosome occurs is now known to be much more complex than the picture given in the previous map. The present map is based upon the published literature through June of 1988. There are now 1,403 loci placed on the linkage group, which may represent between one-third and one-half of the genes in this organism.